Competition Policy, Capacity Building, and Selective Adaptation: Lessons from Japan's Experience - Richard Schwindt; Devin McDaniels (Washington University Global Studies Law Review, 2008)
One potential tool to assist in this regard is Potter’s selective adaptation model. The model identifies the role of local conditions in the adaptation of foreign rules. It has been successfully applied to China’s adaptation of property law, administrative law, and corporate governance rules. The question we address is whether and how the model can be applied to the adaptation of competition policy. This Article reflects our first steps towards an answer.
Keywords: Antitrust law; Economic development -- Developing countries; Transition economies; Economic change